ANALISIS WACANA PERCAKAPAN DALAM KOMEDI SITUASI THE IT CROWD SERI 1 - , YASHINTA FARAHSANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research describes the analysis of conversation in the English conversation transcription of the situational comedy The IT Crowd season 1. The researcher examines four problems, 1) the discourse of dialogue in the conversation transcription of the situational comedy The IT Crowd season 1, 2) the conversation organizations in the conversation transcription of the situational comedy The IT Crowd season 1, 3) the contexts in the conversation transcription of the situational comedy The IT Crowd season 1, 4) the breaking of cooperative principle in the situational comedy The IT Crowd season 1. In analyzing the research data, the researcher utilized the theory of conversation by Cutting (2008: 26), the theory of dialogue discourse by Wijana (1995: 330-331), the theory of exchange structure by Cutting (2008: 22), the theory of conversation analysis by Cutting (2008: 22), Levinson (1983: 287) and Finnegan (1992: 315), and also the theory of context by Cutting (2008: 5). The researcher utilized the observation method to observe the language used in the conversation transcription of the situational comedy The IT Crowd season 1. Next, the researcher utilized the transcribing technique to transcribe the conversation in that situational comedy. Then, the data was categorized into dialogues and conversation. In the dialogue category, it was divided into two categories, one-turned-complex dialogues and multiple-turned-complex dialogues. After that, those dialogues were categorized based on the steps of dialogue process: initiation (I), respond (R), and feedback or follow-up (F). In the conversation category, the data were divided into two categories based on the turn to speak: turn-taking and adjacency pairs. Besides that, the conversations were also categorized based on the sequences: opening, insertion, and closing. From this research, the researcher can conclude three results: 1) the conversations in this situational comedy belong to complex dialogues, including oneturned- complex dialogues and multiple-turned-complex dialogues. In a dialogue, there are three steps: initiation (I), respond (R), and feedback or follow-up (F). In fact, not all the dialogues were closed by F, and not all of them follow the sequence: I-R-I-R (F). 2) Some natural things happen and distract the organization of CA that consists of turn-taking, adjacency pairs, and sequences, such as interruption, overlap, attribute silence, repair, and dispreferred. The process of conversation depends on the participants themselves. 3) Context as the basic of participantsâ understanding in doing a conversation is divided into three: situational context, background knowledge context, and co-textual context. From each type of context, the researcher can observe the relationship of each participant. The closer their relationship, the easier they understand the conversation. 4) The cooperative principles is intentionally broken to create the humor.